Evaluation of thyroid nodules classified as Bethesda category III on FNAC - Shiwani Garg (Journal of Cytology, 2017)
Background: The Bethesda (BSRTC) category III has been ascribed a malignancy rate of 5-15%, however, the probability of malignancy remains variable. Aim: To evaluate category III with respect to its rate and risk of malignancy and substratify it. Settings and Design: Atypia of undetermined significance/Follicular lesion of undetermined significance (AUS/FLUS) percentage, cytohistological correlation, and risk of malignancy were analyzed and substratification was done. Material and Methods: Category III cases over a 2-year period were analyzed retrospectively. Statistical Analysis: Two-tailed Fisher exact test, with a level of significance set at 0.05, was performed for data analysis. Results: Of 1169 thyroid fine needle aspirations (FNAs), 76 (6.5%) were category III. A total of 48 patients had follow up; 24 patients underwent surgery, 12 repeat FNA, and 12 were clinically followed. Repeat FNA cytology was unsatisfactory in 8.3%, benign in 66.7%, AUS in 8.3%, and follicular neoplasm in 16.7%. Of the 24 operated, 8 (33.3%) were malignant (follicular variants of papillary thyroid carcinoma), 5 (20.8%) were follicular adenomas, and 11 (45.8%) were non-neoplastic. Among all AUS/FLUS nodules with follow-up, malignancy was confirmed in 16.7% (8/48) whereas with nodules triaged to surgery only, the malignancy rate was 33.3% (8/24). Substratification into categories of "cannot exclude PTC" and "favor benign" helped detect malignancy better, as 85.7% cases in the first subcategory (P < 0.001) and none (P < 0.02) in the last proved malignant. Conclusion: Though the rate of Category III in our study is in accordance to BSRTC, the risk of malignancy in AUS/FLUS nodules is higher. Substratification of AUS/FLUS may help better patient management.